2013
DOI: 10.1111/ecc.12077
|View full text |Cite
|
Sign up to set email alerts
|

Patient participation in the medical decision-making process in haemato-oncology - a qualitative study

Abstract: Cancer patients are showing increased interest in shared decision-making. Patients with haematological illnesses, however, express considerably less desire for shared decision-making as compared with other oncological patient groups. The goal of the current project was to identify the reasons for the lower desire for shared decision-making among patients with haematological illness. We conducted qualitative, semi-structured interviews with 11 haematological patients (39-70 years old) after the beginning of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 25 publications
1
27
0
2
Order By: Relevance
“…Five interviewed participants once; two interviewed them around diagnosis then at different stages of treatment (Friis, Elverdam, & Schmidt, ; Nissim et al., ). Three focused on patients' information needs (Friis et al., ; Gansler et al., ; Nissim et al., );others addressed information needs in the context of decision‐making (Ernst et al., ), distress (Nissim et al., ) or experiences of watchful waiting (Evans, Ziebland, & Pettitt, ), receiving bad news (Randall & Wearn, ) and the transition from inpatient to ambulatory care (Nissim et al., ). All qualitative papers described inductive approaches to analysis, including domain analysis, constant comparison, grounded theory and thematic content analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five interviewed participants once; two interviewed them around diagnosis then at different stages of treatment (Friis, Elverdam, & Schmidt, ; Nissim et al., ). Three focused on patients' information needs (Friis et al., ; Gansler et al., ; Nissim et al., );others addressed information needs in the context of decision‐making (Ernst et al., ), distress (Nissim et al., ) or experiences of watchful waiting (Evans, Ziebland, & Pettitt, ), receiving bad news (Randall & Wearn, ) and the transition from inpatient to ambulatory care (Nissim et al., ). All qualitative papers described inductive approaches to analysis, including domain analysis, constant comparison, grounded theory and thematic content analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Among the quantitative papers, seven explicitly stated the conceptual background of the study. These included patient‐centred communication (Arora et al., ), shared decision‐making (Ernst et al., ; Gansler et al., ; Poe et al., ) and survivorship (Friedman et al., ; Oerlemans et al., ). Gansler et al.…”
Section: Resultsmentioning
confidence: 99%
“…Women struggled to understand why they were asked to make such an important decision, especially when their clinical team indicated (by words or gestures) their relief when the patient made the ‘right’ decision. More recently, Ernst et al . conducted a qualitative study with 11 haemato‐oncology patients living in Germany and found that the patients were often overwhelmed by the complexity of the illness and the therapy and did not want to assume any responsibility in medical decision making.…”
Section: Introductionmentioning
confidence: 99%
“…This raises an interesting ethical debate regarding how much or how little prognostic information should be discussed and whether a patient's requirement regarding the volume and nature of information discussed should be established prior to the commencement of treatment. Ernst et al (2013) found that haematology patients were often overwhelmed by the complexity of the illness and the therapy and did not want to assume any responsibility in medical decision-making. Participants in their study (Ernst et al 2013) reported a great deal of distress and very traditional paternalistic role expectations with regards to their health care providers, which limited their ability to partake in the decisionmaking process.…”
Section: Medical Talkmentioning
confidence: 99%
“…Ernst et al (2013) found that haematology patients were often overwhelmed by the complexity of the illness and the therapy and did not want to assume any responsibility in medical decision-making. Participants in their study (Ernst et al 2013) reported a great deal of distress and very traditional paternalistic role expectations with regards to their health care providers, which limited their ability to partake in the decisionmaking process. Since scientific knowledge and medical know-how regarding stem cell transplantation (SCT) for haematological malignancy is an experimental, highly technical and developing field it is unsurprising that patients are not always involved in treatment choices.…”
Section: Medical Talkmentioning
confidence: 99%